Antibacteririal avtivities of Bacillus cereus and Shigella dysenteriae of white tea extract in several variation of solvents - Asri Widyasanti; Andita Mega Priantiwi; Dadan Rohdiana (Jurnal Penelitian Teh dan Kina, 2016)
Tea is used in the food, cosmetic, and herbal drug industries. White tea is a kind of tea containing a relatively high polyphenol content compared to other kind of tea, and thus has the potential of being used as a natural antibacterial. The objective of this research was to study the antibacterial activity of of  white tea extract in several variation of  13 % (w/v) concentration of solvents to the activity of gram-positive bacteria (Bacillus cereus) and Gram-negative bacteria (Shigella dysenteriae). Laboratorium experimental method was used in this descriptive study. The antibacterial activity study was comprised of estimating inhibition area and total of bacterial growth. The results revealed that white tea extract inhibited bacterial growth, indicating that white tea extract from the n-hexane, ethyl acetate and 96% ethanol solvents could be developed as an antibacterial material. The diameter of the inhibition area to Bacillus cereus bacteria for n - hexane , ethyl acetate, and  ethanol 13 % (w/ v)  solvents were 0.6 mm, 10.5 mm and 1.75 mm, respectively; while for Shigella dysenteriae bacteria were 0,5 mm, 9,86 mm  and 10,6 mm, respectively. The total growth of Bacillus cereus bacteria for n-hexane, ethyl acetate, and ethanol 13 % (w/v) solvent were 1.3 x 107, 6.0 x 106, and  1.1 x 104 CFU / ml , and of Shigella dysenteriae bacteria were  1.0 x 107,  6.5 x 106 and 4.6 x 106 CFU / ml, respectively.